Essential Role for Ethanolamine Plasmalogen Hydrolysis in Bacterial Lipopolysaccharide Priming of Macrophages for Enhanced Arachidonic Acid Release - Gil-de-Gómez, Luis; Astudillo, Alma M.; Lebrero, Patricia; Balboa, María A.; Balsinde, Jesús (Frontiers in Immunology, 2017)
Due to their high content in esterified arachidonic acid (AA), macrophages provide large amounts of eicosanoids during innate immune reactions. Bacterial lipopolysaccharide (LPS) is a poor trigger of AA mobilization in macrophages but does have the capacity to prime these cells for greatly increased AA release upon subsequent stimulation. In this work we have studied molecular mechanisms underlying this phenomenon. By using mass spectrometry-based lipidomic analyses, we show in this work that LPS-primed zymosan-stimulated macrophages exhibit an elevated consumption of a particular phospholipid species, i.e. the ethanolamine plasmalogens, which results from reduced remodeling of phospholipids via coenzyme A-independent transacylation reactions. Importantly however, LPS-primed macrophages show no changes in their capacity to directly incorporate AA into phospholipids via CoA-dependent acylation reactions. The essential role for ethanolamine plasmalogen hydrolysis in LPS priming is further demonstrated by the use of plasmalogen-deficient cells. These cells, while responding normally to zymosan by releasing quantities of AA similar to those released by cells expressing normal plasmalogen levels under the same conditions, fail to show an LPS-primed response to the same stimulus, thus unambiguously demonstrating a cause-effect relationship between LPS priming and plasmalogen hydrolysis. Collectively, these results suggest a hitherto unrecognized role for ethanolamine plasmalogen hydrolysis and CoA-independent transacylation reactions in modulating the eicosanoid biosynthetic response.